اتفاق التحكيم التجاري الدولي في التشريع الج ازئري - قيشي نبيلة (جامعة المسيلة, 2024)
نظرا ألن التحكيم يلعب دورا فعاال في مجال التجارة الدولية، فهو منصوص عليه في كل من القانون الج ازئري و القوانين الدولية، وبما أن اتفاق التحكيم يحاول إقامة العدل بين الطرفين بدال من محاولة االلتزام باعتبارات قانونية خاصة، فقد تم العثور على خصوصيته حتى اآلن في القانون الدولي، إن اتفاقية التحكيم هي التي ال تزال مثيرة للجدل، وبالتالي تجد ثغرات تسمح لألطراف باإلنحراف والتالعب بالقواعد التي تحكمها ، وبما أن اتفاقية التحكيم هي عقد، أود أن ألفت انتباه الباحثين من خالل التطرق إلى جميع القضايا والنقاط المتعلقة بهذه االتفاقية ، بحيث تكون جميع القواعد منصوص عليها في القانون، باإلضافة إلى ما قد تفرضه االتفاقية المنصوص عليها في ق.م ، تشكل هذه االتفاقية أساس نظام قضائي خاص وهي الطريقة المفضلة لحل النزاعات الدولية، ولكن تعزيز هذه االتفاقية يجب أن يحترم تأثيره على األطراف واالمتثال لقواعد التجارة دولي ة. الكلمات المفتاحية : اتفاقية التحكيم ، القرار التح كيمي ، التشريع الجزائر ي ، التجارة الدولية Abstract Since arbitration plays an effective role in the field of international trade, it is stipulated in both Algerian law and international laws and since the arbitration agreement attempts to establish justice between the parties rather than trying to adhere to special legal considerations, its specificity has so far been found in international law. The arbitration agreement is the one that remains controversial and therefore finds loopholes that allow the parties to deviate and manipulate the rules that govern it. Since the arbitration agreement is a contract, I would like to draw the attention of researchers by addressing all the issues and points related to this agreement, so that all the rules are stipulated In law, in addition to what may be imposed by the agreement established in civil law, the agreement forms the basis of a special judicial system and is the preferred method for resolving international disputes, but the promotion of this agreement must respect its effect on the parties and comply with the rules of international trade. Keywords: arbitration agreement, arbitration decision, Algerian legislation, international trade
Keywords: اتفاقية التحكيم ، القرار التح كيمي ، التشريع الجزائر ي ، التجارة الدولية